2021
DOI: 10.14740/cr1322
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitor Therapy Effects in Patients With Heart Failure With Preserved and Mid-Range Ejection Fraction

Abstract: Background There is hypothesis that endothelial function enhancement is strongly associated with better outcome and functional class improvement in heart failure with preserved ejection fraction (HFpEF) and heart failure with mid-range ejection fraction (HFmrEF) patients. Perindopril is the only angiotensin-converting enzyme inhibitor (ACEI) drug with proven positive effect on the endothelium in coronary artery disease (CAD) patients. In patients with HFpEF and HFmrEF, its impact is still unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Perindopril is the only ACEI that has been shown to improve endothelial function. Notably, Safonova et al demonstrated that after 12-month therapy with perindopril, ET-1 level decreased significantly in both HFpEF and HFmrEF patients [ 100 ]. In addition, other studies have shown that captopril and lisinopril caused a significant reduction in ET-1 production [ 101 , 102 ].…”
Section: Endothelin-1: a Promising Biomarker In Ahfmentioning
confidence: 99%
“…Perindopril is the only ACEI that has been shown to improve endothelial function. Notably, Safonova et al demonstrated that after 12-month therapy with perindopril, ET-1 level decreased significantly in both HFpEF and HFmrEF patients [ 100 ]. In addition, other studies have shown that captopril and lisinopril caused a significant reduction in ET-1 production [ 101 , 102 ].…”
Section: Endothelin-1: a Promising Biomarker In Ahfmentioning
confidence: 99%